PENGARUH PENGELOLAAN KEARSIPAN TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KOTA AMBON - Tri Santi Nova Lewaherilla; Ambarwati Soetiksno; Jean Rosalina Asthenu (P3M Politeknik Negeri Ambon, 2025)
The archive storage system at the Ambon City Regional Financial and Asset Management Agency Office uses an alphabetical storage system, where when a letter is requested, the name of the agency is mentioned using an agenda book. Archival facilities at the Ambon City Regional Finance and Asset Management Agency still lack a place to store archives, as evidenced by the large number of archive stacks in each employee's workspace and are only tied using ropes, while the filing cabinets and archive shelves are fully filled. Archival officers are less dexterous in handling archives. When the Head of the Agency needs a file, the rediscovery of the letter takes quite a long time, approximately 5-10 minutes.A sample of 37 people was taken from employees of the Ambon City Regional Finance and Asset Management Agency. Data is collected by means of observation, interviews and distributing questionnaires to employees. The analysis method used is a simple linear regression analysis using the help of SPSS 25.0 software. The results of the t-test stated that the variable coefficient of Archives Management was 3.940 and the significant value was 0.000 or (<0.05).Based on the results of the study, it can be concluded that the variables of archive management have a positive and significant influence on work effectiveness. This means that if Archive Management increases, work effectiveness will also increase and vice versa, if archive management decreases, work effectiveness will decrease. Keywords: Archive Management and Work Effectiveness